Dispersion free photoelectron wavepackets in multiphoton ionization - Muddukrishna, Pavan (My University, 2025)
One of the ultimate goals in atomic, molecular and optical physics is understanding and controlling molecular chemical reactions which occur on extremely small spatio-temporal timescales. Experimentally observing the breaking and shaping of molecules is difficult and requires a camera which operates at times equal to or less than the molecular timescales. This state of the art camera is called the laser. Coupling it with the Chirped Pulse Amplification (CPA) technique allowed for the development of sub-picosecond pulses with high intensities. This advancement allowed for the rise of imaging techniques via electron rescattering such as Laser Induced Electron Diffraction (LIED) and theories such as Quantitative Rescattering (QRS) theory which have allowed for the extraction and analysis of molecular structure at high electron return energies (hundreds of eV). This dissertation studies an enhancement in electron yield within the rescattering plateau observed from experimentally collected Above Threshold Ionzation (ATI) photoelectron spectra in the multiphoton ionization regime using LIED. The driving mechanism behind this phenomena has remained a mystery for the last 30 years. This dissertation first aims to understand experimental data and the enhancement through theoretically generated High Harmonic Generation (HHG) spectra. The time dependent behavior of the electronic wavepacket was studied when it returned to the parent ion. Rigorous analysis revealed the generation of a bimodal attosecond dispersion free electronic wavepacket at specific wavelengths and intensities that behaved similarly to the generation of a femtosecond pulse within a mode-locked oscillator. Additionally, it was found classical electron rescattering models, which are widely used to explain strong field phenomena, could not explain the electrons’ dynamics and the enhancement within the multiphoton regime. The discovery of the dispersion free wavepacket reframes rescattering processes in the multiphoton regime. The second part of this dissertation involves applying the dispersion free wavepacket to QRS for the extraction of electron-ion differential cross sections (DCS) from experimentally collected photoelectron angular distributions (PADs) at low electron return energies (tens of eV). PADs were collected of argon and smaller hydrocarbons at 1030 nm using a Double-sided Time of Flight (DTOF) Vacuum chamber. The dispersion free wavepacket and QRS theory were subsequently used to extract electron yield representative of an electron-ion DCS. Further comparison with theory is still needed. This application takes the first steps in determining the viability of LIED and Quantitative Rescattering (QRS) theory as methods to extract molecular structure at low electron return energies. Furthermore it helps establish LIED’s ability to image simpler hydrocarbons before proceeding towards more complex organic compounds.
Keywords: Wavepackets; Strong field physics; Laser induced electron diffraction; High harmonic generation; Dispersion; Ionization